Self-crystallization mechanism of perovskite films for improving performance of perovskite solar cells. (June 2023) - Chen, Yichuan; Gao, Hao; Gao, Hongli; Han, Chang Bao; Hu, Yuehui; Yan, Hui
Highlights: The self-crystallization and self-repair characters of perovskite thin films were revealed. The association mechanism was systematically studied between the self-crystallization and the improving of the PSCs photovoltaic performances. The self-crystallization of perovskite films could optimize grain orientation, reduce defects density and Urbach energy, and increase carrier fluorescence lifetime and transportation. Abstract: When the perovskite solar cells (PSCs) had been stored in glove box for 2 days, the improvement of devices performance was observed. The mechanism of this phenomenon was systematically studied by using the in-situ XRD and in-situ absorption spectrum in this paper. It was revealed that the self-crystallization and self-repair characters of (FAPbI3 )1- x (MAPbBr3 ) x films were the keys to improve devices performance at room temperature. Then, we systematically studied the effects of self-crystallization based on grain orientation, crystalline quality, optical absorption properties, Urbach energy, defects density, carrier fluorescence lifetime etc. After self-crystallization, the defects density of (FAPbI3 )1- x (MAPbBr3 ) x thin films was decreased by about 22.9%, the carrier fluorescence lifetime was extended by about 1.68 times, and the Urbach energy was also reduced. These results indicated that the self-crystallization and self-repair of perovskite films could suppress the defect-assisted recombination, reduce the V OC loss, and enhance carrier transportation properties, which contributed to the improvement of the PSCs photovoltaic performance. Graphical abstract: Image, graphical abstract The self-crystallization and self-repair characters of (FAPbI3 )1- x (MAPbBr3 ) x films was revealed by using the in-situ XRD and in-situ absorption spectrum in this paper. The self-crystallization and self-repair of perovskite films could suppress the defect-assisted recombination, reduce the V OC loss, and enhance carrier transportation properties. which contributed to the improvement of the PSCs photovoltaic performance.